Social media and brand image: a longitudinal study of Eastern Cape universities - Mnqeta, Lusanda (Rhodes University, Faculty of Commerce, Rhodes Business School, 2020)
It is important for Higher Education Institutions to have marketing strategies that focus on understanding the customer needs in the 21st century. The rapid growth of the internet and the Web 2.0 have led individuals and organisations into applying social media as a branding and communication tool. Hence this study focused on comparing the influence of social media on four Eastern Cape universities in relation to social media metrics and visually demonstrated through the computer-generated human face, the Chernoff faces. Using diary and literature study, the study adopted a case study research design. The researcher sampled four universities using a purposeful sampling technique. Chernoff faces were used to enhance the ability of the reader to immediately understand significant occurrences based on social media metric indicators. To demonstrate multivariate data, the faces brought an original method of expressing complex data as opposed to traditional methods. The study found that Brand management and Resource-Based Theory (RBT) plays a pivotal role in social media marketing as this can lead to organisations having a competitive advantage. The study recommended that strategies to utilise social media as a resource should be put in place to lead to competitive advantage, as suggested by the Resource-based theory. The study concluded that various social media factors can influence the brand image of universities, positively (going to buy) and negatively (never going to buy). Both positive and negative purchase intent are found to be an influential indicator on the brand as they are affected by customer satisfaction.
Keywords: Multivariate analysis -- Graphic methods; Branding (Marketing) -- South Africa; Chernoff faces; Social media -- South Africa; Universities and colleges -- South Africa -- Marketing; Universities and colleges -- South Africa -- Marketing -- Case studies